Peningkatan Akses Pendidikan Menengah Berorientasi Keadilan di Kabupaten Pati Jawa Tengah - Suroso Suroso (IAIN Ponorogo, 2018)
Abstract: Education is very important to develop human resources. The objective of this study is to analyze the defelopment policy for access equity of secondary education. This research uses descriptive-quantitative approach. The data consist of primary and secondary ones. Data collecting is conducted by using observation and interview. The analysis of data uses descriptive one. There are 3 findings in the research. Firstly, the distribution of secondary education development in the study area is less equally. Secondly, the district which becomes a priority of secondary education development is the district which has the smallest ratio between proportion of existing secondary education toward proportion of population. Thirdly, the most potential site for the secondary education development oriented to optimazation accessibility is the site in the centre by incorporating geographical factor and population. However, selecting a land of the site for secondary education development should meet the normative standards in the regulation.ملخص: إن التربية مهمة لتطوير الموارد البشرية. حاول هذا البحث تحليل قرار تعميم الحصول على التربية في المرحلة المتوسطة. واستخدم هذا البحث المدخل الوصفي الكيفي. وتشتمل بيانات البحث على البيانات الأساسية والبيانات الثانوية. وهذه البيانات تُجمع عن طريق الملاحظة والمقابلة. أما طريقة تحليلها فبالتحليل الوصفي. حصل الباحث على نتائج البحث، أولا: إن تعميم البناء التربوي للمرحلة المتوسطة في موضع البحث لم يكن شاملا للجميع، ثانيا: إن المنطقة كالهدف للبناء التربوي للمرحلة المتوسطة لها اتجاه للعدالة، هي المنطفة التي لها نسبة أصغر بين نسبة وجود التربية للمرحلة المتوسطة تجاه نسبة المواطنين، وثالثا: المنطقة الممكنة للبناء التربوي للمرحلة المتوسطة المتجه إلى التعميم التربوي هي المنطقة الوسطى باعتبار الموقع الجغرافي والمواطنين. ولكن اختيار المكان للبناء التربوي للمرحلة المتوسطة هذا لابد من استيفاء المعايير النظامية.